2017
DOI: 10.1017/s1751731116001622
|View full text |Cite
|
Sign up to set email alerts
|

Invited review: Relationship between cattle transport, immunity and respiratory disease

Abstract: The association between transportation and the occurrence of the bovine respiratory disease complex (BRDC) has long been recognised. Many hypotheses regarding this association have been declared through the past decades, and it is agreed upon by most researchers that the multiple stressors that calves experience during transportation result in an overall immunosuppression that allows the respiratory tract to be invaded by numerous opportunistic pathogens. Furthermore, the innate immune cells, neutrophils, may … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
69
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 79 publications
(69 citation statements)
references
References 49 publications
0
69
0
Order By: Relevance
“…Bovine respiratory disease complex (BRDC), also known as shipping fever, is the most common infectious disease affecting older weanling, stocker, or feeder calves causing extensive economic losses to the North American beef and dairy cattle industry [15,16]. BRDC develop as a complex interaction between environmental stress factors, host factors, and multiple viral and bacterial infectious agents [17]. Various viral pathogens such as bovine herpes virus-1, bovine viral diarrhea virus, bovine respiratory syncytial virus, bovine parainfluenza-3, bovine coronavirus and bovine adenoviruses have been implicated to predispose calves to secondary bacterial infections.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Bovine respiratory disease complex (BRDC), also known as shipping fever, is the most common infectious disease affecting older weanling, stocker, or feeder calves causing extensive economic losses to the North American beef and dairy cattle industry [15,16]. BRDC develop as a complex interaction between environmental stress factors, host factors, and multiple viral and bacterial infectious agents [17]. Various viral pathogens such as bovine herpes virus-1, bovine viral diarrhea virus, bovine respiratory syncytial virus, bovine parainfluenza-3, bovine coronavirus and bovine adenoviruses have been implicated to predispose calves to secondary bacterial infections.…”
Section: Introductionmentioning
confidence: 99%
“…Various viral pathogens such as bovine herpes virus-1, bovine viral diarrhea virus, bovine respiratory syncytial virus, bovine parainfluenza-3, bovine coronavirus and bovine adenoviruses have been implicated to predispose calves to secondary bacterial infections. The most important bacterial pathogens associated with BRDC are Mannheimia haemolytica, Pasteurella multocida, Histophilus somni, and Mycoplasma bovis [15,17]. Each of these bacteria are commensals in the nasopharynx of cattle.…”
Section: Introductionmentioning
confidence: 99%
“…Lastly, a great limitation of the study is that it was not possible to split the effects of the stress due to transport from stress due to the adaptation to a new farm and to document how those stressors affect the immune system of the animals. It has been found that potential causes for BRD onset include stress associated with transport, adaptation to feed, the new social hierarchy, and viral exposure [1,2]. It is well known that these stressors affect respiratory immunity, response to infection, bacterial growth, viral replication and the tissue repair process, and are responsible for an increase in cortisol release and a decrease in leukocyte numbers [20,21].…”
Section: Discussionmentioning
confidence: 99%
“…The syndrome has a multifactorial etiology, including infectious agents, host and environmental factors, with particular emphasis on transport stress. The latter is indeed responsible for physiological changes that favor pathogen proliferation and invasion of tissues by opportunistic pathogens [1][2][3][4][5]. Viruses and stress-related behavior interfere with the mucociliary clearance of the respiratory tract and dysregulate the tracheal antimicrobial peptides of the innate defenses, allowing opportunistic bacteria to cause pulmonary infections [2,6].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation